Penanaman Nilai-nilai Religius melalui Kegiatan Keagamaan Majelis Ta’lim Perumahan Graha Mangun Masjid Nurul Yaqin - Husin, Malik (Universitas Pahlawan Tuanku Tambusai, 2025)
Majelis Ta’lim is a strategic form of religious activity aimed at fostering spiritual values and shaping social attitudes within the community. This activity seeks to enhance the understanding and practice of religious values in daily life, particularly for women as key educators in the family. By delivering religious themes, Majelis Ta’lim creates an educational and reflective atmosphere while strengthening social bonds among participants. This community service program employed a lecture method combined with a Participatory Action Research (PAR) approach, emphasizing empowerment and active community involvement. The results indicate that Majelis Ta’lim is not only effective as a medium for religious education outreach but also plays a significant role in increasing religious awareness and social solidarity within the community. These findings highlight the importance of sustaining similar programs as a contextual and practical means of empowerment based on Islamic values.